The chameleon wore chartreuse : from the tattered casebook of Chet Gecko, private eye - Hale, Bruce (San Diego : Harcourt, 2000)
When hired by a fellow fourth-grader to find her missing brother, Chet Gecko uncovers a plot involving a Gila monster's revenge upon the school football team.
"Ages 8 to 12"--cover p. [4].
410
Keywords: Geckos -- Fiction; Lizards -- Fiction; Schools -- Fiction; Lost and found possessions -- Fiction; Mystery and detective stories